INVESTIGATING THE IMPACT OF HEALTH INFORMATICS ADOPTION ON RADIOLOGISTS' DIAGNOSTIC ACCURACY AND TURNAROUND TIME: A CROSS-SECTIONAL STUDY IN SAUDI ARABIAN HOSPITALS - Ahmed Theyab Albathali, Anwr Hammoud AlRuwaili, Fahad Mufleh AlRuwaili, Hessah Ghazi Ayesh Albogami, Khalid Nasser Mansoor Almutairi, Naif Hamed Hagar Almutairi, Saleh Hassan Ali Almohawis, Sultan Waqf AlRuwaili, (Chelonian Research Foundation, 2022)
Health informatics has become increasingly important in modern healthcare, with the potential to improve patient outcomes and optimize clinical processes. This cross-sectional study aimed to investigate the impact of health informatics adoption on radiologists' diagnostic accuracy and turnaround time in Saudi Arabian hospitals. A sample of 200 radiologists from 20 hospitals across the country was surveyed using a validated questionnaire. The study utilized logistic regression analysis to examine the relationship between health informatics adoption and diagnostic accuracy, and multiple linear regression analysis to assess the association between health informatics adoption and turnaround time. The findings revealed that higher levels of health informatics adoption were significantly associated with improved diagnostic accuracy (OR=1.85, 95% CI: 1.32-2.59, p<0.001) and reduced turnaround time (β=-0.42, 95% CI: -0.58 to -0.26, p<0.001), after controlling for confounding variables such as radiologist experience and hospital size. The study highlights the potential benefits of health informatics in enhancing radiologists' performance and suggests that investing in health informatics infrastructure and training can lead to improved patient care and efficiency in Saudi Arabian hospitals. Keywords: health informatics, diagnostic accuracy, turnaround time, radiologists, Saudi Arabia